2018
DOI: 10.30954/0424-2513.3.2018.7
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Agroforestry Systems for Livelihood Security and their Economic Appraisal in Indian Himalayas

Abstract: Sustainable indigenous agroforestry systems are mainstay of rural agrarian economy coupled with livestock rearing in mountains of Himalayas. A 2B4D6-watershed was selected in Central Himalayas to investigate economic returns from agriculture based agroforestry systems. A detailed structured analysis revealed four types of agriculture based agroforestry systems are prevalent in the 2B4D6-watershed of Indian Central Himalaya. These agroforestry systems are profitable to farmers and can obtain more than twofold r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…By limiting reliance on marketplace changes of particular crops, farmers' revenue instability is mitigated through diversification. Many research conducted worldwide ( [41]; [42]; [43] have shown that the availability of multiple sources of revenue contributes to the greater economic stability reported by households practicing agroforestry. Since diverse products, which protect farmers from income shocks, such as timber, fodder fruits, nuts, and non-timber forest products, become sources of income in addition to traditional crop [44].…”
Section: Socioeconomic Impactsmentioning
confidence: 99%
“…By limiting reliance on marketplace changes of particular crops, farmers' revenue instability is mitigated through diversification. Many research conducted worldwide ( [41]; [42]; [43] have shown that the availability of multiple sources of revenue contributes to the greater economic stability reported by households practicing agroforestry. Since diverse products, which protect farmers from income shocks, such as timber, fodder fruits, nuts, and non-timber forest products, become sources of income in addition to traditional crop [44].…”
Section: Socioeconomic Impactsmentioning
confidence: 99%
“…India has diversified climate, different agricultural conditions and abundant wasteland in villages need to be considered while implementing various methods of forestry. Various agroforestry practices can be used based on climate of the place and utility, benefits and on need basis [7,9,19].…”
Section: Agroforestry and Climate Changementioning
confidence: 99%
“…Therefore, at present the agro-forestry tree planted portion will not only prevent soil erosion but also increase its productive power and will help to maintain environmental balance. Planting trees with crops will increase the returns from per unit land [19].…”
Section: Agroforestry and Climate Changementioning
confidence: 99%